Preoperative anxiety during COVID-19 pandemic: A single-center observational study and comparison with a historical cohort - Buonanno, Pasquale; Marra, Annachiara; Iacovazzo, Carmine; Vargas, Maria; Nappi, Serena; de Siena, Andrea Uriel; Servillo, Giuseppe (Frontiers in Medicine, 2022)
Background Preoperative anxiety is a common sensation experienced by patients undergoing surgical interventions. It can influence intraoperative and postoperative management through the activation of the neuroendocrine system, leading to tachycardia, hypertension, pulmonary complications, higher consumption of anesthetic drugs, and increased postoperative pain. Our aim was to investigate the level of preoperative anxiety during the COVID-19 pandemic; we also compared it to the preoperative anxiety of a historical cohort before the outbreak. Methods This is a single-center observational study. We enrolled 314 patients during the pandemic from May 2021 to November 2021, and our historical cohort consisted of 122 patients enrolled from July 2015 to May 2016 in the university hospital “Federico II” of Naples. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) and the State-Trait Anxiety Inventory (STAI) were used to evaluate preoperative anxiety. In particular, APAIS measures preoperative anxiety and the need for information, and STAI assesses state and trait anxiety through STAI-Y1 and STAI-Y2, respectively. We analyzed APAIS and STAI scores in our population stratified on the basis of age, gender, marital status, previous surgical experiences, and type of surgery, and we compared them to our historical cohort. Statistical analysis was performed through a t-test and ANOVA for parametric data, and the Mann–Whitney and Kruskal–Wallis tests for non-parametric data. Linear regression was used to investigate the correlation between demographic data and the scores of STAI and APAIS in both groups. Results Our results showed that state and preoperative anxiety remained stable, whereas trait anxiety increased in all the subgroups analyzed. Discussion Even if state anxiety is considered a variable characteristic of the emotional sphere and trait anxiety a stable element, our findings suggested that COVID-19 deeply influenced trait anxiety, thus altering the patients’ psychological foundations.